Harmonizing Local Wisdom with Islamic Values: A Guide to Character Education Development - Baderiah, Baderiah; Munawir, Ahmad (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
The globalization wave has caused Indonesians to gradually lose and forget the values of local wisdom as the nation's assets and charm. The global community recognizes Indonesia as a society characterized by positive traits such as friendliness, courtesy, industriousness, altruism, openness, courage, and others. Initial observations at the State Islamic Institute of Palopo indicate that lecturers perceive that most students have lost the original character of the Indonesian nation. Implementing character education aligned with local wisdom values can address this issue. The research employed in this study is developmental research with the four D (4 D) model. Data collection techniques used include direct observation, interviews, and questionnaires. We can overcome negative student character issues using local wisdom and religious values. Every higher education institution requires character education guidelines that lecturers can use as a reference to cultivate positive student character. Higher education institutions can conduct character education through lectures, academic guidance, and real-life community service activities.